International cooperation on migration in Africa in the 1950s: an analysis of UN High Commissioner for Refugees reports - Selivanov, Andrey V. (Journal of the Belarusian State University. International Relations, 2024)
This article analyses United Nations High Commissioner for Refugees reports to the United Nations General Assembly (sessions 6–16), examining international cooperation on forced migration in Africa through UN High Commissioner for Refugees activities. The study concludes that the 1950s marked the beginning of dynamic international cooperation in migration. As decolonization began, migration patterns shifted towards forced displacement. UN High Commissioner for Refugees, initially responsible for a small number of persons of concern, gradually expanded its programmes across regions. States and international organisations supported these efforts through resettlement and local assistance programmes. The Algerian crisis highlighted the need to broaden the scope of the 1951 Convention relating to the status of refugees. The 1950s can be divided into two distinct phases: 1951–1956, when international bodies first engaged with African migration issues, and 1957–1960, marked by an active emergency response to forced migration.